2013
DOI: 10.1002/clc.22089
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Evaluation of Catalytic Iron in Patients With Acute Coronary Syndromes

Abstract: Background: The potential of iron to generate reactive oxygen species has motivated a long-standing interest in whether excess iron is causally linked to atherosclerotic heart disease. Circulating catalytic iron (''free'' iron) is that which is not bound to transferrin or ferritin and is available to generate reactive oxygen species that may have deleterious vascular effects. Hypothesis: We hypothesized that increased levels of catalytic iron would be associated with increased cardiovascular events. Methods: W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Although AKI is a well known risk factor for increased hospital mortality (30), five of the nine patients who died in the hospital did not have AKI, raising the possibility that catalytic iron may be toxic to multiple organ systems and not just the kidneys. Consistent with this possibility, elevated plasma catalytic iron levels are associated with increased mortality in other settings, including patients with acute coronary syndrome (15,16).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Although AKI is a well known risk factor for increased hospital mortality (30), five of the nine patients who died in the hospital did not have AKI, raising the possibility that catalytic iron may be toxic to multiple organ systems and not just the kidneys. Consistent with this possibility, elevated plasma catalytic iron levels are associated with increased mortality in other settings, including patients with acute coronary syndrome (15,16).…”
Section: Discussionsupporting
confidence: 55%
“…In humans, the release of intracellular stores of iron under conditions of tissue injury (3) or hemolysis (11) results in elevated circulating levels of catalytic iron. High plasma catalytic iron levels, in turn, may have a pathologic role in a variety of disease states, including coronary artery disease (12,13) and acute coronary syndrome (14)(15)(16); however, the association with AKI has not been well studied in humans.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is suggested that only the catalytic iron pool is involved on iron-induced oxidative stress through the Fenton reaction. Catalytic iron levels in plasma are two orders of magnitude below the levels found for total plasma iron [34,35]. Thus, despite evidencing effects of NAC/DFX on plasma iron levels, we suggest that a more accurate assay should be employed in order to unveil the effects of the treatments in the catalytic iron pool.…”
Section: Discussionmentioning
confidence: 87%
“…And total body iron status has a positive association with risk of premature acute myocardial infarction [13]. While in patients with acute coronary syndrome, increased iron levels are associated with increased all-cause mortality [14]. Iron chelation could improve endothelial function in patients with coronary artery disease [15].…”
Section: Discussionmentioning
confidence: 99%